SEISMIC SAFETY EVALUATION OF ABDUL MANNAN OVERPASS IN CHITTAGONG, BANGLADESH (Malaysian Journal of Civil Engineering, 2018)
A number of multi-span overpasses in major cities of Bangladesh, such as Dhaka (the capital city) and Chittagong (the principal seaport city) have been constructed for the last few years with a view to reducing the traffic congestion at critical junctions. Abdul Mannan overpass is one of these, which is located in Chittagong city. It has been launched in the year of 2012 with a prime objective of reducing the traffic congestion within Chittagong city. This study is devoted towards assessing seismic safety of this overpass, which comprises in two phases: the first phase is dedicated towards the evaluation of seismic lateral strength and ductility whereas the second phase is aimed at assessing seismic fragility and retrofit of the overpass. In this regard, the first phase utilizes the ductility method as suggested by Japan Road Association (JRA) to evaluate lateral strength and ductility of piers of the overpass considering their different modes of failure. The lateral strengths of pier sections in bending are obtained based on their nonlinear sectional analyses results, while the shear strengths are estimated using JRA suggested method. The fiber models with conventional constitutive models for concrete and steel are used to obtain the moment-curvature relationships at critical sections of the overpass pier. The pushover analysis method is employed to derive the force-displacement relationships of piers using the results of the moment-curvature relationships. Subsequently, the lateral seismic demand, allowable lateral force, yield displacement, ultimate displacement and displacement ductility are obtained using the standard methods. In the second phase, the nonlinear dynamic analysis of a typical pier of the overpass is carried out for seismic fragility assessment followed by an assessment of seismic retrofit strategy suitable for the overpass. The numerical results of the study indicate that most of the piers of the overpass do not comply seismic safety requirements for design earthquake ground motion rerecords, which warrants the retrofit of piers of the overpass.